"Win & Lose": Rivalitas Media Sosial Vs E-Commerce - Imelda, Rossa Amelia; Amellia, Rizqi; Astuti, Dina Dwi; Defira, Bela Dwi; Azis, Deni Ibnu; Rahmawati, Titi (MDP Student Conference, 2024)
This study aims to determine the advantages and disadvantages by comparing the use of Social Media TikTok Shop vs E-Commerce Shopee. This research was conducted from November 2023 to January 2024 using the literature study method. The observed varia;bles include product prices, features, discount & cashback vouchers, payment methods, packaging & shipping, and reviews. The results showed that Shopee E-Commerce is superior to Tiktok Shop Social Media because Shopee has more complete features, there are many discount vouchers, cashback, payment methods, and delivery service options. Shopee also has its own grouping of goods, there is proof of delivery photos, and when the buyer gives a review, they will get feedback in the form of shopee coins that can be redeemed at checkout. This research also produces a ven diagram of community expectations from the seller and buyer side of TikTok Shop social media and Shopee E-Commerce.